On the Stability of Time-Fractional Schrödinger Differential Equations. (3rd October 2017) - Hicdurmaz, B.; Ashyralyev, A.
ABSTRACT: In the present paper, the exact solution for time-fractional Schrödinger differential equation in a Hilbert space is presented. The stability estimates for the solution of a time-fractional Schrödinger differential equation and its derivatives are obtained. In addition, applications of the stability theorems are given.